Perancangan Infografis Tentang Bahaya HIV/AIDS untuk Mahasiswa di Wilayah Kota Semarang - Lintang Dewi Sekar Kinasih; Daniar Wikan Setyanto (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
HIV/AIDS is a global health problem that threatens the lives of many individuals. The HIV virus attacks the body's immune system, weakening its ability to fight infection and disease, which can then progress to AIDS, the final stage of HIV infection. Although certain treatments can slow the progression of the disease, awareness about the dangers of HIV/AIDS is very important, especially for college students. This knowledge can help them understand how to prevent transmission, such as practicing safe sex and avoiding sharing needles. In Semarang City, the high number of HIV/AIDS cases shows the need for further efforts to increase public awareness and knowledge, especially in the productive age group. Social stigma against HIV/AIDS sufferers is also a challenge that needs to be overcome through community-based interventions. Infographics published on social media can be an effective means of increasing student awareness about the dangers of HIV/AIDS, which is expected to contribute to preventing transmission and improving the quality of life of affected individuals. The aim of this research is to convey clear, accurate and easy to understand information to the public, with the hope of increasing awareness about the risk of transmission, symptoms, prevention and treatment of HIV/AIDS. The methodology used is qualitative. The result of this research is to create an infographic design about the dangers of HIV/AIDS via social media for students in the Semarang city area.